2010
DOI: 10.1111/j.1365-294x.2010.04873.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history of the conifer root rot fungus Heterobasidion annosum sensu lato

Abstract: We investigated two hypotheses for the origin of the root rot fungus Heterobasidion annosum species complex: (i) that geology has been an important factor for the speciation (ii) that co-evolutionary processes with the hosts drove the divergence of the pathogen species. The H. annosum species complex consists of five species: three occur in Europe, H. annosum s.s., Heterobasidion parviporum and Heterobasidion abietinum, and two in North America, Heterobasidion irregulare and Heterobasidion occidentale; all wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 44 publications
(62 reference statements)
2
98
0
Order By: Relevance
“…We also observed a greater accumulation of iron in P. sylvestris roots in response to exposure to H. annosum s.s. than in response to the other two species . Heterobasidion parviporum and H. abietinum are genetically related to each other more closely than to H. annosum s. s. (Karjalainen 1996;Kasuga et al 1993), which was confirmed by evolutionary studies by Dalman et al (2010). This can explain the similar response of the host to H. parviporum and H. abietinum.…”
Section: Discussionsupporting
confidence: 70%
“…We also observed a greater accumulation of iron in P. sylvestris roots in response to exposure to H. annosum s.s. than in response to the other two species . Heterobasidion parviporum and H. abietinum are genetically related to each other more closely than to H. annosum s. s. (Karjalainen 1996;Kasuga et al 1993), which was confirmed by evolutionary studies by Dalman et al (2010). This can explain the similar response of the host to H. parviporum and H. abietinum.…”
Section: Discussionsupporting
confidence: 70%
“…species complex has been studied using several different genetic markers (Garbelotto et al, 1996;Harrington et al, 1998;Kasuga and Mitchelson, 2000;Maijala, 2000;Johannesson and Stenlid, 2003;Linzer et al, 2008). (Dalman et al, 2010) proposed an evolutionary hypothesis for the H. annosum s.l. species complex where it originated in Laurasia and that the H. annosum s.s./H.…”
Section: Introductionmentioning
confidence: 99%
“…Migration and allopatric separation later lead to the development of the pine infecting species H. annosum s.s. and H. irregulare in Europe and North America, respectively. Although through a different migration route H. occidentale established and developed in North America while further separation in sympatry leads to the development of H. parviporum and H. abietinum in Europe which is reflected in the current species distribution (Dalman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the different species have been separated for up to 75 million years (Dalman et al, 2010), they have retained a high degree of interfertility and a wide range of host species. This means potentially dire consequences if a species should be successfully introduced in a foreign environment.…”
Section: Natural Hybridisation In North America and Italymentioning
confidence: 99%